Digital transformation and sustainable performance: the mediating role of triple-A supply chain capabilities - Mohaghegh, Matin; Blasi, Silvia; Russo, Ivan; Baldi, Benedetta (The Journal of business & industrial marketing, 2025)
Purpose Drawing on resource orchestration theory, this paper aims to empirically investigate the relationships between digital transformation (DT), triple-A supply chain capabilities (i.e. agility, adaptability and alignment) and sustainable performance. The research focuses on the pharmaceutical industry, which best represents a business environment characterized by volatility, uncertainty, complexity and ambiguity. Design/methodology/approach Data were collected at different echelons of a globally oriented pharmaceutical supply chain, with the focal company located in the Netherlands. Empirical data were analyzed with partial least squares – structural equation modelling. Findings The findings reveal that DT enhances the triple-A supply chain capabilities. Nevertheless, not all three capabilities are necessary to improve overall sustainable performance. The results highlight that, among the three, only supply chain agility and adaptability significantly mediate the relationship between DT and sustainable performance. Originality/value This research supports the literature affirming that not all the triple-A supply chain capabilities equally affect sustainable performance. Moreover, it deepens the understanding of how orchestrating the triple-A capabilities at a firm level fosters overall sustainable performance, facing resource scarcity and investments in DT.